Does The Psychology of Investment Decisions Depend on Risk Perception And Financial Literacy? - Anifa, Anis Sukha; Soegiharto, Soegiharto (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
This study examines and analyses the effect of overconfidence, herding effect, and disposition effect bias on investment decisions mediated by risk perception and moderated by financial literacy. The sample for this study uses 184 investors from 19 provinces in Indonesia using a purposive sampling technique. Regression partial least squares test the hypothesis with the Warp-PLS application version. The study's results found that overconfidence bias does not affect risk perception. Herding effect bias and disposition bias have positive effects on risk perception. Risk perception has a positive effect on investment decisions. Risk perception fully mediates the relationship between disposition effect bias on investment decisions. However, risk perception does not mediate the relationship between overconfidence bias and herding effect bias on investment decisions. Meanwhile, financial literacy must moderate the relationship between risk perception and investment decisions. The implication of the study is expected to assist the Financial Services Authority in increasing investors' financial literacy in the capital market.